Penerapan Sistem Prategang pada Perancangan Struktur Bentang Panjang Gedung Poltekkes Mataram - Wijanarko, Riza; Hariyadi, Hariyadi; Fitrayudha, Adryan (Jurnal Talenta Sipil, 2025)
The Mataram Poltekkes building located in Mataram, West Nusa Tenggara consists of 4 floors with a total height of 16.8m. The entire floor of this building uses a reinforced concrete structure, which makes it vulnerable to lateral forces, especially those caused by earthquakes. Earthquakes are at risk of causing building damage, therefore a strong structure is needed to carry the load of the structure and put pressure on the beams structure. One method to strengthen the structure is by using prestressed beams. This research was conducted by changing the design of the beams structure from conventional to prestressed beams structure. The research problems in this study is how the comparison of the weight efficiency of buildings using conventional beams with prestressed beams and how the effect of prestressed beams on the stretch between columns. so that researcher get the purposes of knowing the comparison of the weight efficiency of buildings using conventional beams with prestressed beams and knowing the effect of prestressed beams on the stretch between columns. In this study, a general type of data collection method was used, namely data collection carried out by collecting working drawings from project service providers. The results of the analysis showed that the prestressed beams used concrete with a compressive strength of 50 MPa, dimensions of 1.6 m x 0.6 m and an initial prestress force of 400 kN. These prestressed beams experienced a loss of prestress force of 12.87%. The number of tendons used is 1 tendon with a total of 4 strands in one tendon. The weight of the building using prestressed beams is lighter than conventional beams with an efficiency of 7.471%. In conclusion, buildings using prestressed beams are more efficient than using conventional beams